Ribotype Classification of Clostridioides difficile Isolates Is Not Predictive of the Amino Acid Sequence Diversity of the Toxin Virulence Factors TcdA and TcdB - Li, Zhenghui; Lee, Kwok; Rajyaguru, Urvi; Jones, C. Hal; Janezic, Sandra; Rupnik, Maja; Anderson, Annaliesa S.; Liberator, Paul (Frontiers in Microbiology, 2020)
Clostridioides (Clostridium) difficile is the most commonly recognized cause of infectious diarrhea in healthcare settings. Currently there is no vaccine to prevent initial or recurrent C. difficile infection (CDI). Two large clostridial toxins, TcdA and TcdB, are the primary virulence factors for CDI. Immunological approaches to prevent CDI include antibody-mediated neutralization of the cytotoxicity of these toxins. An understanding of the sequence diversity of the two toxins expressed by disease causing isolates is critical for the interpretation of the immune response to the toxins. In this study, we determined the whole genome sequence (WGS) of 478 C. difficile isolates collected in 12 countries between 2004-2018 to probe toxin variant diversity. A total of 44 unique TcdA variants and 37 unique TcdB variants were identified. The amino acid sequence conservation among the TcdA variants (> 98%) is considerably greater than among the TcdB variants (as low as 86.1%), suggesting that different selection pressures may have contributed to the evolution of the two toxins. Phylogenomic analysis of the WGS data demonstrate that isolates grouped together based on ribotype or MLST code for multiple different toxin variants. These findings illustrate the importance of determining not only the ribotype but also the toxin sequence when evaluating strain coverage using vaccine strategies that target these virulence factors. We recommend that toxin variant type and sequence type (ST), be used together with ribotype data to provide a more comprehensive strain classification scheme for C. difficile surveillance during vaccine development objectives.